NMR pD-variation method to determine the proper stabilities of organic electrolyte complexes: case of histidine complexes with a cyclophane acid. Issue 10 (3rd October 2021) - Navarro, Rosa Elena; Soberanes, Yedith; Inoue, Motomichi
ABSTRACT: The complexation of organic electrolytes, like carboxylic acids and amines, is studied usually by spectrometric titration at a constant pH. Obtained stability constants are, however, conditional and dependent on the pH selected, differing from the proper constants. In nuclear magnetic resonance (NMR) titration in D2 O, a stability constant determined at a given pD is not directly correlated to other properties observed at a pH in H2 O because of difference between acid dissociations in the solvents. To overcome these problems, this report proposes pD-variable NMR spectrometry, which monitors NMR signals of a mixture of the reactants with the variation of pD. This method identifies complexes formed in different pD ranges, and determines the proper stability constants, to yield the species distribution, which can be replotted in pH scale. The usefulness and limitation are examined by simulation of titration curves. An experimental example is presented for complexation of histidine with a cyclophane acid. Excel® files for calculations are available in Supplementary material. Graphical Abstract: uf0001